IMPLEMENTATION OF JIGSAW MODEL VISITING OUT OF CLASS IN IMPROVING STUDENTS’ LEARNING OUTCOMES OF WRITING DESCRIPTIVE (A STUDY AT THE VIII.1 STUDENTS OF SMP NEGERI 4 PADANGSIMPUAN - Della Febrina (JURNAL LINER (Language Intelligence and Educational Research), 2022)
This Classroom Action Research was motivated by the low learning outcomes of Writing Descriptive Objects in Class VIII.1 Students of SMP Negeri 4 Padangsidimpuan, which was improved by the Application of the Jigsaw Model Visiting Out of Class. The formulation of the problem in this research is "How Can the Application of the Jigsaw Model Visiting Out of Class Improve Learning Outcomes in Writing Descriptions of English Objects in Class VIII.1 of SMP Negeri 4 Padangsidimpuan"? The purpose of this study was to improve the learning outcomes of writing English object descriptions through the application of the jigsaw model for visiting outside the classroom in class VIII.1 of SMP Negeri 4 Padangsidimpuan. The expected benefits in this study are (1). For students to improve learning outcomes and create a new atmosphere in the learning process that is fun. (2). For teachers it can be an additional reference for learning models that can be tried out in their respective schools, as an effort to get it easier to write descriptions of simple objects in carrying out English learning. Each cycle goes through the stages of planning, implementation/action, observation and reflection. The research subjects were class VIII -1 students of SMP Negeri 4 Padangsidimpuan in the odd semester of 2019/2020 with a total of 23 students consisting of 10 male students and 13 female students. The final results of this study indicate that the application of the jigsaw model visiting outside the classroom improves learning outcomes in writing descriptions of objects. Keywords:Jjigsaw Model,Students Learning Outcomes, Descriptive